PESTS OF ORNAMENTAL TREES OF THE LEGUMINE FAMILY (Leguminosae) IN THE REPUBLIC OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This article describes in detail the levels of occurrence, bioecological features, and also the distribution of pests in ornamental trees belonging to the legume family.